Associations Between Different Cortisol Measures and Adiposity in Children: A Systematic Review and Meta-Analysis - Ma, Lu; Liu, Xi; Yan, Na; Gan, Yiqun; Wu, Yue; Li, Ying; Chu, Meng; Chiu, Dorothy T.; Ma, Le (Frontiers in Nutrition, 2022)
This study examined associations between hair, salivary, serum, and urinary cortisol with adiposity-related indicators in children, and explored their potential effects modification by age, sex, cortisol extraction method, and country developmental context. We systematically searched PubMed, Web of Science, and Embase for studies examining at least one of the four aforementioned cortisol with objectively measured adiposity-related outcomes in children. Meta-analyses of cross-sectional studies revealed that hair cortisol concentration was associated with fat mass index (FMI)-standard deviation score (SDS)/FMI z-score (pooled-β=0.04, 95%CI: 0.01, 0.08) and BMI/BMI z-score (pooled-β=0.15, 95%CI: 0.06, 0.25), and these associations were significant among children aged ≤12 years (pooled-β=0.15, 95%CI: 0.05, 0.26) and >12 years (pooled-β=0.13, 95%CI: 0.04, 0.22), children from developed countries (pooled β=0.12, 95%CI: 0.03, 0.21) and developing countries (pooled-β=0.193, 95%CI: 0.188, 0.198), and in studies extracting cortisol via LC-MS/MS (pooled-β=0.18, 95%CI: 0.06, 0.29) but not ELISA (pooled-β=0.08, 95%CI: -0.06, 0.22). Meta-analyses of both cohort and cross-sectional studies revealed non-significant associations of morning salivary cortisol and total daily cortisol output with BMI/BMI z-score. Serum cortisol was not associated with BMI or waist circumference. Meta-analysis of urinary cortisol and adiposity was hindered by insufficient data. These findings further corroborate understanding of chronic stress’ physiological contribution to increased pediatric obesity risk.